2020
DOI: 10.3389/fmars.2020.00179
|View full text |Cite
|
Sign up to set email alerts
|

Heat Waves Are a Major Threat to Turbid Coral Reefs in Brazil

Abstract: Coral reefs are threatened by climate change on a global scale with thermal stress events and mass coral bleaching being widely reported. The reefs off the east coast of Brazil (and other turbid areas) have, however, historically escaped such thermal stress events, with relatively low levels of background coral mortality (5-10%). This has recently changed. Here we show that, in 2019, degree heating weeks (DHW) of 19.65 coincided with catastrophic declines in coral cover, especially in the major reef building h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 34 publications
0
48
0
Order By: Relevance
“…Further evidence for the resilience of South Atlantic reefs is that a heat stress of 7.7 • C-weeks (degree heating weeks, which accounts for the accumulation of temperature anomalies exceeding the monthly maximum mean Liu et al, 2006;Kayanne, 2017) caused 20% coral mortality in the Caribbean (Florida Keys) and 13 • C-weeks caused 80% mortality in Indo-Pacific (Australia) reefs, however, a remarkable value of 20 • C-weeks, ranking among the highest ever recorded, resulted in less than 2% mortality in the marginal reefs of the Southwestern Atlantic (Gilmour et al, 2013;Gintert et al, 2018;Banha et al, 2019). And even more recently, in late 2019, 19.6 • C-weeks recorded for the diverse Abrolhos reefs caused no significant mortality for any reef-building species with the exception of the branching and fast-growing hydrocoral Millepora alcicornis and, to a lesser extent, the phacelloid Mussismilia harttii, further highlighting the resilience of South Atlantic reefs to heat stress (Duarte et al, 2020). Two additional advantages are that the South Atlantic is historically and currently less exposed to heat waves (Skirving et al, 2019) and that the largest reefs in the South Atlantic are found in the Abrolhos Bank, which is systematically influenced by cooler-water eddies that reduce thermal stress (Ghisolfi et al, 2015).…”
Section: Mortality Associated With Bleaching Episodesmentioning
confidence: 93%
See 1 more Smart Citation
“…Further evidence for the resilience of South Atlantic reefs is that a heat stress of 7.7 • C-weeks (degree heating weeks, which accounts for the accumulation of temperature anomalies exceeding the monthly maximum mean Liu et al, 2006;Kayanne, 2017) caused 20% coral mortality in the Caribbean (Florida Keys) and 13 • C-weeks caused 80% mortality in Indo-Pacific (Australia) reefs, however, a remarkable value of 20 • C-weeks, ranking among the highest ever recorded, resulted in less than 2% mortality in the marginal reefs of the Southwestern Atlantic (Gilmour et al, 2013;Gintert et al, 2018;Banha et al, 2019). And even more recently, in late 2019, 19.6 • C-weeks recorded for the diverse Abrolhos reefs caused no significant mortality for any reef-building species with the exception of the branching and fast-growing hydrocoral Millepora alcicornis and, to a lesser extent, the phacelloid Mussismilia harttii, further highlighting the resilience of South Atlantic reefs to heat stress (Duarte et al, 2020). Two additional advantages are that the South Atlantic is historically and currently less exposed to heat waves (Skirving et al, 2019) and that the largest reefs in the South Atlantic are found in the Abrolhos Bank, which is systematically influenced by cooler-water eddies that reduce thermal stress (Ghisolfi et al, 2015).…”
Section: Mortality Associated With Bleaching Episodesmentioning
confidence: 93%
“…), which are typically branching and inhabit very shallow depths (Amaral et al, 2006;Santos et al, 2016;Teixeira et al, 2019). Only a single mass coral mortality episode has been recorded for the South Atlantic reefs (also mostly associated with Millepora spp., despite occurring in turbid conditions Duarte et al, 2020) and none of the three major global mass bleaching events that affected the Indo-Pacific and Caribbean had comparable effects in the South Atlantic (Kelmo et al, 2003;Teixeira et al, 2019). Further evidence for the resilience of South Atlantic reefs is that a heat stress of 7.7 • C-weeks (degree heating weeks, which accounts for the accumulation of temperature anomalies exceeding the monthly maximum mean Liu et al, 2006;Kayanne, 2017) caused 20% coral mortality in the Caribbean (Florida Keys) and 13 • C-weeks caused 80% mortality in Indo-Pacific (Australia) reefs, however, a remarkable value of 20 • C-weeks, ranking among the highest ever recorded, resulted in less than 2% mortality in the marginal reefs of the Southwestern Atlantic (Gilmour et al, 2013;Gintert et al, 2018;Banha et al, 2019).…”
Section: Mortality Associated With Bleaching Episodesmentioning
confidence: 99%
“…While nearshore dominance of zoanthids seems related to higher turbidity baselines [ 33 , 85 ] and positive feedback from high abundances (“abundance refuge”, sensu [ 86 ]), it is remarkable that their relative cover steadily increased only in SGOM, which is under the direct influence of a major dredging operation since 2002 (see S2 Text ). Zoanthid dominance seemed conditioned to local chronic stress, while thermal anomalies are likely the major source of stress at the regional scale [ 26 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the ecological functions performed by nearshore habitats are deteriorating rapidly due to the cumulative impacts of multiple human disturbances (e.g. Copertino et al., 2016; Cruz et al., 2018; Duarte et al., 2020; Giglio et al., 2015; Gorman et al., 2020; Magris & Giarrizzo, 2020; Magris et al., 2019). Our study therefore demonstrates the utility of the cumulative impact maps in developing integrated conservation planning and offers critical insights for the strategic implementation of conservation actions in Brazil.…”
Section: Discussionmentioning
confidence: 99%